Usulan Strategi Pengembangan Bisnis pada Startup Unggascare - Deandrie Ramadhanti; Kristina Sisilia; Imanuddin Hasbi; Agus Maolana Hidayat; Fauzan Aziz (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Startups in Indonesia are growing rapidly. Startups are created to solve problems that exist in society. This is because startups are created because there are problems and solutions so that they can produce ideas to solve and anticipate these problems. Developing a startup in Indonesia is not easy, so new strategies are needed so that startups are better prepared to face competition. The aim of this research is to identify the strategies needed for future business development at the Unggacare startup. The research method used is qualitative methodology with descriptive research. These results were obtained using observation, interview and documentation techniques.The results of this research show that carrying out business development can be done using the SWOT method, in which case there are internal factors and external factors that can support all the company's needs. Unggascare uses SWOT, which contains strengths, weaknesses, opportunities and threats that can form strategies to develop the company so that it can grow in the livestock industry. Unggascare is in the Grow and Build position, this shows that the Unggascare startup company is able to grow and build, so it still needs to examine internal and external factors in order to support the strategies that need to be carried out by Unggascare.